Cultural differences and entrepreneurial needs - Wanasika, I.; Bakker, D.; Wehner, R.; Ahmed, G.; Bakhadirov, M.; Liu, H. J.; Rong, L.; Tsuzuki, Y.; Dubickis, M.; Treacy, S.; Kharusi, S. A.; Silva, M. G.; et al. (Würzburg International Business Forum: 6th International Business Conference, 2023)
The purpose of this study was to investigate entrepreneurial intentions and cultural differences. The sample represents 1,110 business students from ten cultural clusters. The students completed a questionnaire that focussed on various dimensions of entrepreneurial intentions. Results indicated various statistically significant differences between the cultures. Country specific strategies related to enhancing entrepreneurship are discussed at the end of the paper.